To Investigate The Prevalence And Incidence Of Anaemia And Its Comorbidities In The Gandhinagar Population (Journal of Pharmaceutical Negative Results, 2022)
Background: Anaemia is a major public health issue that affects 2 billion people worldwide, affecting people of all ages and genders. According to the WHO, iron deficiency anaemia is the leading cause of anaemia, accounting for 50% of all cases.Methodology: An observational study was carried out at Gandhinagar, Gujarat from November 2015 to March 2016. A complete blood count (CBC) report of patients were collected directly from patient’s laboratory report and entered in structured case report form. The Questionnaire, to obtain information regarding life style, food habits, socioeconomic status and medical history was filled by the patients.Results: A total of 521 patient’s data were collected in which 146 (48.66%) males and 154 (51.33%) females were suffering from anaemia. In anaemic patients 131 (43.66%) patient were microcytic anaemic, 125 (41.66%) were normocytic and 44 (14.66%) patient were macrocytic anaemic. Out of 300 anaemic patients, 231 (76.15%) were in age group of 16-50 years. Majority of patients seems to be suffering from the nutritional anaemia due to poor consumption of diet. Majority of anaemic patients belonged to upper-middle class and upper-lower class family. There were no significant differences of the smoking, tobacco, alcohol consumption with anaemia.Conclusion: According to our data, poor dietary habits seem to be major cause for anaemia. Lack of awareness about the disease worsens the problem. Awareness programs at community levels by health agencies can significantly help in reducing the burden of the diseases.